Testing the Effectiveness of Herbal Mouthwash Made from Betel Leaves and Kalamansi Orange - Iwan Iskandar; Hevi Horiza; Mutia Yuhesti (Aloha International Journal of Health Advancement (AIJHA), 2025)
The oral cavity is the most complex and easily accessible site for microbial colonization in the human body. Teeth, gingiva, tongue, and buccal mucosa have different surfaces for microbial colonization. To reduce microbes in the oral cavity, medicinal plants can be used. Medicinal plants that can be utilized include Betel Leaves and Kalamansi orange. Betel leaves are well-known in Indonesian society not only for their traditional consumption but also for their widespread availability throughout Indonesia. The study aimed to develop a new mouthwash candidate using organic materials without the addition of alcohol compounds. This research was a laboratory experimental study, involving the preparation of betel leaf extract, the production of Betel Kalamansi Mouthwash (Sirkala), and testing the Betel Kalamansi Mouthwash (Sirkala) against two types of bacteria, Streptococcus mutans and Bacillus cereus, compared to the patented Listerine mouthwash. The stages include organoleptic testing and data processing. The expected outcome of this research is the development of an alcohol-free mouthwash made from organic materials. Microbiological effectiveness test results show that the herbal mouthwash formula Sirkala can effectively eliminate the target bacteria Streptococcus mutans, with a killing ability of up to 99.999% at contact times of 10, 15, and 20 seconds. This is comparable to the results of testing Listerine mouthwash widely available in the market. However, based on testing against Bacillus cereus, the herbal mouthwash formulation Sirkala is unable to eliminate the target bacteria like Listerine mouthwash. Keywords: efficacy testing; herbal mouthwash; betel leaf; calamansi orange